Improved CO2 Capture and Catalytic Hydrogenation Using Amino Acid Based Ionic Liquids. Issue 23 (27th October 2022) - Moazezbarabadi, Ayeshe; Wei, Duo; Junge, Henrik; Beller, Matthias
Abstract: A series of alkyl ammonium (or imidazolium) based ionic liquids was tested as novel and potentially green absorbent for CO2 capture and utilization. By exploiting various amino acids as counter ions for ionic liquids, CO2 capture and hydrogenation to formate occur with high activity and excellent productivity utilizing arginine. The reaction was easily scalable without any significant drop in formate production, and the catalyst was reused for five consecutive runs leading to an overall TON of 12, 741 for the formation of formate salt. Abstract : Nice catch ! A system for the capture and subsequent hydrogenation of CO2 to formate that utilizes amino acid‐based ionic liquids and a homogeneous Ru catalyst in water/THF was reported. The low vapor pressure, nontoxic nature, and high reactivity of amino acid‐based ionic liquids toward carbon dioxide made them ideal for absorbing CO2 even from ambient air and converting it to value‐added products.